KINETICS ASSESSMENT OF LOCALISED CORROSION DAMAGES IN PIPE WELDS OF WATER-STEAM CIRCUIT ELEMENTS - Дмитрах, Ігор Миколайович; Колодій, Богдан І.; Білий, Орест Левкович; Лещак, Ростислав Любомирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Localised damaging of power unit components under long-term exploitation essentially impact on their reliability and safety. Nowadays, there are number problems among which the localised corrosion of water-steam circuit elements is the actual. Present work is devoted to problem of local corrosion of the welded joints of dissimilar pipes (low-alloyed pearlite steel 12Х1МФ and austenitic stainless steel Х18Н10Т). Based on analytical determination of corrosion current density distribution on the external pipe’s surface, the model and numerical procedure for kinetics assessment of localised corrosion damages was developed. As results the depth of corrosion damaging as function of time has been received for the welded zone area with take into account the environmental composition variables and materials degradation during term of exploitation. The length of corrosion activity zone at the weld has been also assessed. Evaluated model and received data can be served as basis for prediction of the given welded joint behaviour during long-term exploitation with the aim to prevent the catastrophic situations.